Core-shell nanoparticles toughened polylactide with excellent transparency and stiffness-toughness balance. (18th August 2018) - Chen, Yuan; Pan, Mingwang; Li, Yue; Xu, Jia-Zhuang; Zhong, Gan-Ji; Ji, Xu; Yan, Zheng; Li, Zhong-Ming
Abstract: Polylactide has attracted increasing focus on packaging and other consumer products nowadays, due to its stiffness, biodegradability and good transparency. However, its toughened blends are usually utilized to conquer its inherent brittleness, unfortunately, bringing with undesirable opaqueness. Considering the transparency and toughness of PLA, nanoparticles with core-shell structure, which are one kind of methyl methacrylate–butyl acrylate (ACR) copolymers whose rubbery cores resist impact and the glassy shells provide rigidity and compatibility to the polymer matrix, were manipulated by seed emulsion polymerization in this work, aiming to toughen PLA without the substantial decrease of transparency and tensile strength simultaneously. The effects of size and content of ACR nanoparticles on the optical properties, mechanical properties of PLA/ACR blends respectively were clarified. The PLA/ACR blends exhibited excellent transparent property with a transmittance as high as 75% (550 nm). We found an unexpected relationship between particles size and transparency, that is, with the decrease of ACR size, the transparency of blends was also reduced slightly. This phenomenon may contribute to the scattering of bigger aggregation formed by ACR with smaller size, which was identified by microstructure observations. Tensile testing showed the maximum elongation at break of 279.9% when ACR content reached 20 wt%, which was a 65-fold increase compared with neat PLA. Promisingly, the elastic modulus and tensile strength exhibited less decreased with the value of 55.7 MPa and 2.06 GPa respectively, and this blends displayed 8 times the Izod impact strength over neat PLA. It was revealed the shear yielding of matrix and cavitation of particles during the loading process led to the excellent toughness of PLA/ACR blends. Graphical abstract: Image 1